(untitled) (World Bulletin of Social Sciences, 2025)
This article discusses the causes of pre-competition stress in athletes, its psychological and physiological consequences, as well as effective methods for reducing stress. The psychological tension observed before competitions is considered an important factor that negatively affects an athlete’s performance. Therefore, increasing the psychological preparedness of athletes and developing mechanisms for managing stress are among the priority directions of modern sport psychology. The article analyzes the practical effectiveness of methods such as autogenic training, visualization, breathing techniques, music relaxation, positive thinking, and team-based psychological support. The results of the study show that regular application of these methods strengthens athletes’ mental stability, develops self-regulation skills, and contributes to improved competition performance. In addition, the article highlights the role of coaches and sport psychologists in reducing stress and emphasizes the importance of individual work with athletes. In conclusion, it can be stated that the application of scientifically grounded psychological methods to reduce pre-competition stress is an essential factor for achieving high results in sports.